Public acceptance of COVID-19 vaccination among residents of Saudi Arabia: a cross-sectional online study. Issue 10 (31st October 2022) - Almeshari, Meshari; Abanomy, Ahmad; Alzamil, Yasser; Alyahyawi, Amjad; Al-Thomali, Asma W; Alshihri, Abdulaziz A; Althomali, Omar W
Abstract : Objectives: The acceptance of the COVID-19 vaccine is essential for protecting the world population and stopping the COVID-19 pandemic. This paper aimed to measure public acceptance of the COVID-19 vaccination and the factors that may play an important role in increasing the acceptance of vaccinations in future pandemics. Design: A cross-sectional, observational study was conducted through a survey designed using the Google Forms platform. In this study, a logistic regression analysis was used to study and detect the variables linked to the acceptance of COVID-19 vaccination. To meet inclusion criteria, participants had to be 18 years or older at the time of collecting the data, reside in Saudi Arabia at the time of the survey, agree to the consent form and be able to complete the survey in Arabic. Setting: Randomly selected residents of Saudi Arabia. Number of participants: 1658. Results: In general, the population of Saudi Arabia is supportive of the COVID-19 vaccine (72.0%) and has one of the highest acceptance rates, according to global studies. We found that men (OR 0.73; 95% CI: 0.55 to 0.97) were less likely to hesitate with regard to taking the vaccine, whereas previously infected individuals were more likely to hesitate (OR 1.77; 95% CI: 1.25 to 2.50). Those with a lower monthly income (<3000 Saudi riyal) were more likely to refuse the vaccine (OR 3.54; 95% CI: 1.81 to 6.91), while those living in cities (OR 0.62; 95% CI: 0.39 to 0.99) and the unemployed (OR 0.52; 95% CI: 0.33 to 0.83) were less likely to refuse it. Participants' history of viral infection and trust in the healthcare system were found to be important factors in the public's acceptance of the vaccine. Conclusion: In general, acceptance of the COVID-19 vaccination is high in Saudi Arabia. Several factors have shown a method for predicting those who might reject the vaccine or hesitate to take it; thus, the healthcare system should target those residents throughout the campaign. Based on the conclusions of the current research, the acceptance of vaccinations could be increased.